ASSESSMENT INDEKS LEAN DAN GREEN PADA SMEs COKELAT BEAN TO BAR DI INDONESIA - Siti Aisyah, Machfud, Sukardi, Ono Suparno (Department of Agroindustrial Technology, Bogor Agricultural University, 2018)
The development of chocolate Small Medium Enterprises (SMEs) is very strategic for Indonesia, where trade transactions value of processed cocoa and chocolate contributes to foreign exchange> USD 1 Billion/year. The demands of industrial operational systems that are slender (lean) and environmentally friendly (green) will be very important issues to be resolved particularly by SMEs with all their limitations. The purpose of this study was to determine the level of practice of lean and green on chocolate bean to bar SMEs in Indonesia and determine the importance of experts on the implementation of lean and green on chocolate bean to bar SMEs in Indonesia. The results of the analysis of the lean practice level on chocolate bean to bar SMEs with a scale of 1 - 5, obtained a lean practice level obtained a scale of 3.85 and green practice of 3.39, while the scale of importance for lean is 4.41 and for green is 4.5. This indicates that the achievement index of lean and green practices are in the value of 3.62 which means that SMEs cocoa bean to bar Indonesia has not fully implemented the practices of lean and green.Keywords : practice lean, practice green, SMEs, chocolate industry, bean to bar, LG Index